Myxopapillary ependymoma in a 6-year-old girl with paraplegia- timely intervention enabled complete recovery - Rajeshwari, N.; Savitha, A.; Prahada, J.; Rajkumar, S.; Nandini, G. (International Journal of Contemporary Pediatrics, 2021)
Intramedullary spinal cord tumors accounts for 4-10% of all central nervous system tumors and 35-40% of all intraspinal tumors in children. Biological behavior of these tumors is slow progression and often may not be recognized till they have attained significant size. Back pain, motor weakness, frequent falls and gait disturbances are the presenting complaints. Myxopapillary ependymoma is WHO grade 1 tumor associated with very good prognosis. Early diagnosis and complete surgical resection are the treatment of choice. We reported this case to emphasize the fact that appropriate diagnosis and complete surgical resection of the intraspinal tumor in a child with paraplegia with acute retention of urine with grade 0 power enabled complete neurological recovery.